WOMEN AND SYNCHRONIZED ROLES - Nazire Müge SELÇUK (Fırat University, 2019)
Women's rights is a concept which has been commonly discussed since 1960's until today. Besides, feminist movement played a significant role in the process that the concept of ‘women's rights’ has gained a meaning. In the most general sense, it is possible to define feminism as the opinion which is opposed to gender discrimination and advocates primarily social equality, and the political and economic togetherness between two genders. Feminist movement studies in the role of womanhood in the art history which has been established by bringing female artists into the forefront and rejecting the social gender codes on the other hand and examines the components of the family structure as an institution. “The reality that the established and accepted order is in general determined by men and imposed on women is forcing modern women to adopt some new attitudes”(Atagok, 2011, p.19). Patriarchal traditions and social taboos have made women and men two extremes of the same story and discriminated two genders for centuries. However, women are currently present in every field of life as the most important element of the society. Primarily the epoch-making article of Linda Nochlin named 'Why Have There Been No Great Women Artists' and other studies of feminist critics and art historians on the traditional art history have seriously suspended the process of ignoring the production of women artists. The fact that women artists have brought the objects in their daily life into question as the artistic topics and materials contributes in the process of formation of a new style of expression in the art history. Moreover, a common language has been created by putting emphasis on women sensibility, life experience, accumulation, opinions and emotions with the feminist attitude. By this way, women artists are allowed to orient to new pursuits and some other new materials and they add new spheres in the art with an experimental attitude. The basis of this study named as “Women and Synchronized Roles” is composed of the questioning of taught/learned values in the context of women and art. In this regard, the experimental art is used as the method of the study.